Reconstructing Democratic Inclusive Education Through National Culture and Humanistic Values: A Critical Interpretive Synthesis from Indonesia - Mukhammad Wahyudi; Agus Darmawan; Sevilla Dian Mumtaz (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
Inclusive education in Indonesia faces persistent tension between global normative commitments and systemic implementation gaps, compounded by efforts to align international inclusion frameworks with the constitutional ethos of Pancasila and Bhinneka Tunggal Ika, Indonesia's foundational principles of unity in diversity. Disability-centered models have largely failed to accommodate Indonesia's democratic and cultural specificities, leaving a conceptual void in policy and pedagogical practice. This study reconstructs inclusive education as a democratic, cultural, and humanistic project through Critical Interpretive Synthesis (CIS). This methodology generates interpretive and theory-building outputs from qualitative and mixed-methods evidence, and was applied to 111 studies published between 2014 and 2026. The synthesis yielded a conceptual model termed culturally grounded democratic humanism, integrating four constructs: inclusivity, democratic education, national culture and local wisdom, and humanistic character. Three core propositions are advanced. First, national cultural frameworks, Pancasila, Bhinneka Tunggal Ika, gotong royong (communal cooperation), and local wisdom function not as curricular ornaments but as an ethical grammar that structures institutional governance, social relations, and learning design. Second, humanistic character constitutes the internal telos of inclusive education, operationalized through five capacities: relational dignity, critical empathy, cooperative solidarity, dialogical courage, and ethical responsibility. Third, the model bridges critical inclusive theory, Indonesian constitutional values, and humanistic pedagogy into a coherent architecture, avoiding both abstract universalism and cultural parochialism. The framework offers a culturally grounded alternative to disability-based paradigms and a testable conceptual architecture for inclusive education policy, school governance, and pedagogical practice across Indonesian educational levels and comparable democratic-pluralist societies